A Novel Capsule Endoscopic Score for Crohn's Disease. Issue 2 (17th May 2020) - Omori, Teppei; Matsumoto, Takayuki; Hara, Toshifumi; Kambayashi, Harutaka; Murasugi, Shun; Ito, Ayumi; Yonezawa, Maria; Nakamura, Shinichi; Tokushige, Katsutoshi
Abstract: Background and Aims: The Lewis Score (LS) and Capsule Endoscopy Crohn's Disease Activity Index (CECDAI) are the two currently used small bowel capsule endoscopy (SBCE) scoring systems for Crohn's disease (CD). The present study describes a new scoring system for evaluation of small bowel CD, especially mucosal inflammation. Methods: In this cross-sectional study, 108 CD patients underwent 196 SBCEs. The small bowel lesions were scored using our new Crohn's Disease Activity in Capsule Endoscopy (CDACE). CDACE is the sum of scores for location of inflammation, range of inflammation, and stenosis, with a value ranging from 0 to 1643. We analyzed the relation between CDACE and LS, CECDAI, CDAI, and CRP values and evaluated the inter-rater reliability of CDACE using the intraclass correlation coefficient (ICC) (2.1). Results: The mean (±SD) values of LS, CECDAI, and CDACE were 501 ± 1177, 5.8 ± 5.4 and 431 ± 356, respectively. CDACE correlated significantly with LS and CECDAI ( ρ = 0.737, P < 0.0001 for LS and ρ = 0.915, P < 0.0001 for CECDAI). CDACE also correlated significantly with CDAI ( ρ = 0.36) and CRP ( ρ = 0.23). The ICC (2.1) was 0.829, indicating strong agreement among readers. Conclusions: CDACE is a potentially useful SBCE scoring system for small bowel CD, as it represents the extent and spread of small bowel mucosal inflammation and stenosis. Lay Summary: Crohn's disease (CD) exhibits a wide variety of pathologies, including inflammation and stenosis. An ideal scoring system that properly evaluates CD must consider stenosis and inflammation factors separately. The novel score represents the extent of small bowel inflammation and stenosis.